Hubungan Teman Sebaya dan Paparan Media Sosial dengan Perilaku Fast Food Pada Siswa - Rahmasari, Fanny Arya; Ismah, Zata; Agustina, Dewi (Universitas Malahayati, 2024)
ABSTRACT Fast food behavior in teenagers can be influenced by several factors such as the influence of social media and peers. Peers and social media can influence a person's eating habits because they can introduce or promote fast food directly and indirectly. The purpose of this research is to determine the relationship between interaction with peers, exposure to social media, and fast food behavior among MAN 1 Langkat students, because fast food has become an important part of the eating pattern in various groups, especially among teenagers. This research is a quantitative research with cross-sectional design. The research sample was 59 students. The research instrument used was a questionnaire. Data collection was carried out by filling out questionnaires by respondents. Data analysis was carried out using the Chi-Square test. There is a significant relationship between peers and exposure to social media and fast food behavior among MAN 1 Langkat students. It is recommended to provide education about the importance of healthy eating patterns, encourage students to be more active in physical activities, and provide positive social support to help them reduce their fast food consumption behavior. In this study, the characteristics of the largest number of respondents based on age were obtained, consisting of 44 respondents aged 16 years with a percentage of (74.6%). The characteristics of the largest number of respondents based on gender consisted of 31 respondents in the female category with a percentage of (52.5%). The characteristics of the largest number of respondents based on 1 month's allowance consisted of 57 respondents in the Rp. 500,000 – Rp. 1,000,000 with a percentage of (96.6%). Keywords: Peers, Social Media, Fast Food, Teenagers ABSTRAK Perilaku fast food pada remaja dapat dipengaruhi oleh beberapa faktor seperti pengaruh media sosial dan teman sebaya. Teman sebaya dan media sosial dapat mempengaruhi kebiasaan makan seseorang karena mereka dapat memperkenalkan atau mempromosikan makanan cepat saji secara langsung dan tidak langsung. Tujuan penelitian ini adalah untuk mengetahui hubungan antara interaksi dengan teman sebaya, paparan media sosial, dan perilaku fast food pada siswa MAN 1 Langkat,dikarenakan fast food telah menjadi bagian penting dari pola makan diberbagai kalangan,terutama dilakangan remaja.Penelitian ini adalah penelitian kuantitatif dengan desain cross sectional. Sampel penelitian sebanyak 59 orang siswa. Instrumen penelitian yang digunakan adalah kuesioner. Pengumpulan data dilakukan dengan pengisian kuesioner oleh responden. Analisis data dilakukan dengan uji Chi-Square. Ada hubungan signifikan antara teman sebaya dan paparan sosial media dengan prilaku fast food pada siswa-siswi MAN 1 Langkat. Disarankan untuk menyediakan edukasi tentang pentingnya pola makan sehat, mengajak siswa untuk lebih aktif dalam kegiatan fisik, dan memberikan dukungan sosial yang positif untuk membantu mereka mengurangi perilaku konsumsi fast food. Dalam penelitian ini didapatkan karateristik responden terbanyak berdasarkan umur terdiri atas 44 responden dengan umur 16 tahun dengan persentase sebesar (74.6%). Karateristik responden terbanyak berdasarkan jenis kelamin terdiri atas 31 responden dengan kategori perempuan dengan persentase sebesar (52.5%). Karateristik responden terbanyak berdasarkan uang jajan 1 bulan terdiri atas 57 responden dengan kategori Rp. 500.000 – Rp. 1.000.000 dengan persentase sebesar (96.6%). Kata Kunci: Teman Sebaya, Media Sosial, Fast Food, Remaja